Garrido Gallardo, M. A. (dir.), L. Dolezel et alii, El lenguaje literario. Vocabulario crítico, Madrid, Síntesis, 2009, 1502 pp. - Cabrera, Yoandy (2010)
Fil: Cabrera, Yoandy. Universidad de La Habana; Cuba